The evolution of the use of big data to serve Moroccan territorial economic intelligence - TAJ, TAJ Tilila (Revue du contrôle, de la comptabilité et de l’audit, 2023)
The issue of the sustainable economic and social development of a territory, and its attractiveness, is considered as a major concern of the Moroccan governmental institutions within the new economic development models. In fact, the strategic reforms undertaken as a part of the advanced regionalization system support the ambition to provide each territory the necessary tools and information to respond effectively to the continuous economic, environmental and social challenges. The practice of economic intelligence is based on the control of the information that must be protected, the understanding of opportunities and threats and the coordination between actors and activities. Thus, Big Data supports all these fundamentals targets. The development of new technologies as machine learnings, cloud computing, social networks, internet of things … provides reliable and real-time information about the existing resources and expand operational mechanisms of steering, coordination and evaluation. Successful territories are those built through a continuous exchange network that integrate all the common values, issues and geo-economics strategies of a country. We analyze in this paper, the contribution of Big Data on the development of a territorial economic intelligence by providing the ability to transform a basic “Information” to an ‘InfoAction’ and an ‘OPEN DATA’ connecting the real-time information with the action to execute. Moreover, we conduct a qualitative study about the evolution of the use of Big Data by Moroccan public administrations and its impact on the territorial economic intelligence.